1975
DOI: 10.1111/j.1365-246x.1975.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Mars have a Magnetosphere?

Abstract: Summary The space‐probe plasma and magnetic evidence for Mars having a significant dipole field is uncertain and contradictory. If ionization processes in the planet's exosphere are taken into account, several discrepancies between observation and the fluid model can be explained. The possibility that some solar plasma flows directly into the atmosphere and is there absorbed is still open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The Mariner 4 and 5 fly-by missions to Mars and Venus, respectively, provided the first detailed examination of their ionospheres by means of radio occultation experiments [Kliore et al, 1965; Mars to support the solar wind pressure were' also raised by Gringauz et al [1974], Whitten and Colin [1974], Wallis [1975], Gringauz [1976], Breus and Gringauz [1980], and Gringauz [1980]. However, only Gringauz, Wallis, and Breus have used the lack of ionopause signatures and weaknesses of the ionosphere as evidence for the existence of a significant intrinsic magnetic field.…”
Section: Balancing Solar Wind Dynamic Pressurementioning
confidence: 99%
“…The Mariner 4 and 5 fly-by missions to Mars and Venus, respectively, provided the first detailed examination of their ionospheres by means of radio occultation experiments [Kliore et al, 1965; Mars to support the solar wind pressure were' also raised by Gringauz et al [1974], Whitten and Colin [1974], Wallis [1975], Gringauz [1976], Breus and Gringauz [1980], and Gringauz [1980]. However, only Gringauz, Wallis, and Breus have used the lack of ionopause signatures and weaknesses of the ionosphere as evidence for the existence of a significant intrinsic magnetic field.…”
Section: Balancing Solar Wind Dynamic Pressurementioning
confidence: 99%
“…Several authors have analyzed these data to describe the interaction of solar wind with the atmosphere of Mars (Gringauz et al 1974, Whitten and Colin 1974, Wallis 1975, Breus and Gringauz 1980, Slavin and Holzer 1982, Luhmann et al 1987, Hanson and Mantas 1988, Dubinin et al 1991, Schwingenschuh et al 1992, Shinagawa and Cravens 1992, Fox 1997. The MGS spacecraft has obtained magnetic field and plasma observations throughout the Mars environment from beyond the influence of Mars to just above the surface at an altitude of ∼100 km.…”
Section: Introductionmentioning
confidence: 97%
“…The calculated electric current distribution was similar to that of wind dynamic pressure [Gringauz et al, 1974;Whitten and Colin, Venus. Recently, Luhmann et al [1987] also suggested that the 1974; Wallis, 1975;Gringauz, 1976;Breus and Gringauz, 1980; intrinsic magnetic field is negligible, and that the solar wind-Mars lntriligator and Smith, 1979; Slavin and Holzer, 1982;Luhmann et al, 1987;Hanson and Mantas, 1988]. In fact, the ionospheric thermal pressure near 300 km is exceeded by the typical solar wind dynamic pressure 85% of the time [cf.…”
mentioning
confidence: 99%